Het Amsterdams Grafisch Atelier. (Amsterdam : Amsterdams Grafisch Atelier)
Aardewijn, Renée ; van Alphen, Jacques ; van den Berg, Henk ; Bieruma-Oosting, Jeanne ; Bouws, Ingrid ; van der Deen, Helen ; Dieters, Coos ; van Es, Sonja ; Gaebler, Jo ; geursen, Wilco J. ; Hagenaar, M.J. Herman ; Hardy, Philippe ; van Haren, Elma ; van der Heyden, Peter ; Hofstra, Sjoerd ; Hoogendijk, Wouter ; Kuys, Lucas ; Louwers, Margriet ; van der Mandele, Anneke ; van der Meer, Anneke ; Noorman, Ronald ; Ruijter, Mirjam ; Schutte, Marian ; Simons, Riki ; de Staaij, Janneke van ; Staartjes, Anton ; Worm, Wim ; Wout, Dick van 't
boek